Briefing: Measuring pavement skid resistance – comparing manually pushed and trailer-mounted devices. Issue 4 (17th July 2021) - Stokes, James; Nassar, Ahmed I.; Wright, Michael
Abstract : In 2009, a manually pushed device was developed to measure the dry and wet skid resistance of pavement surfaces at walking pace. The device is based on the same principle as a larger trailer-mounted version and provides a continuous measurement of skid resistance; it is particularly suitable on sites where the survey speed cannot be achieved by trailer- or vehicle-mounted devices. The manually pushed device is also useful for restricted test sections and where the incline, camber or gradient are not desirable for other survey methods. However, the device is not currently covered by a national or international test standard. Its use has also been restricted due to a lack of published research regarding the correlation of results with other methods of measurement. This paper describes on-site testing conducted using the manually pushed device to assess the correlation of the test results with results provided by a trailer-mounted device. The repeatability of the test method and the influence of survey speed on the test results are also examined.